Green Cosmetıcs And Generatıon Z In Indonesıa: The Role Of The IMB Model In Predıctıng Purchase Intentıon - Andika Andika; Nadia Nadia; Della Nanda Luthfiana; Fikri Budi Aulia (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
The development of green cosmetics is considered a transformative step that supports sustainability issues and environmental protection. Furthermore, Generation Z, which is the largest population segment in Indonesia, shows a positive response and concern for sustainability issues. However, a deeper understanding is needed to identify Generation Z's interests in green cosmetics. This is important considering that Generation Z is often seen as a reactionary digital society and is susceptible to being influenced by viral trends in society or on social media, as revealed in several previous studies. This research uses a theoretical framework from the Information-Motivation-Behavioral Skills (IMB) model. Through questionnaires on online survye, data from 264 Generation Z respondents in Indonesia are collected. This data was then analyzed using Descriptive Statistics and Structural Equation Modeling (SEM). The results of the analysis show that product knowledge significantly influences Generation Z's purchase intention. Self-efficacy acts as a mediator between knowledge and purchase intention. In addition, attitudes towards green cosmetics do not directly influence purchase intentions; self-efficacy becomes the bridge connecting attitudes and purchase intentions. The relationship between subjective norms and purchase intention is proven significant, with self-efficacy as the mediator. Meanwhile, although environmental awareness influences purchase intentions, self-efficacy does not mediate this relationship. The IMB model provides a deep understanding of what motivates Generation Z in Indonesia to choose green cosmetics. These findings have significant implications for marketers in promoting green cosmetics to strengthen the self-efficacy of Generation Z consumers in understanding their products.